The Regulator’s Perspectives to Operationalize Maqasid al Shariah: A Case of Pakistan - Rizvi , Ali Abdullah; Jan, Shafi Ullah; Malik, Adnan (The Lighthouse Journal of Social Sciences, 2023)
Islamic financial institutions play a crucial role in promoting Islamic finance. Shariah compliance is a major concern that cannot be compromised under any circumstances. The primary objective of Shariah is to promote a society based on ’falah’, which means well-being or success. Islamic development is based on ’maqasid al Shariah’. It is imperative for Islamic financial institutions to fulfill these objectives of Shariah. Maqasid al Shariah are the higher goals set by Islamic Shariah law, aiming to achieve the well-being of society not only in this world but also in the hereafter. Academia often criticizes Islamic finance for deviating towards a capitalist system instead of focusing on these maqasid, which were the original purpose of Islamic finance. This raises the question of whether the Islamic banking industry and its regulators interpret the concept of maqasid al Shariah in the same way as academia and assign it the same level of relevance and importance. There is a possibility that the Islamic finance industry and regulators perceive, interpret, and practice this phenomenon differently. This study aims to examine how regulators view the concept of maqasid al Shariah and how they put it into practice. The study adopts a constructivist approach and uses a case study methodology, focusing on The State Bank of Pakistan (SBP), the central bank and regulator of the banking system in Pakistan. To develop a framework, a total of 13 in-depth interviews were conducted with Shariah scholars, Islamic banking experts, and policymakers at the Central Bank. The study identifies four perspectives held by the regulator regarding maqasid al Shariah and their implementation: (1) Public welfare (maslahah), (2) Justice/fairness, (3) Shariah compliance, and (4) Government policy.